65.7k views
22 votes
Enter the solution (x, y) to the system of equations shown.

Enter the solution (x, y) to the system of equations shown.-example-1
User Adjanaye
by
5.3k points

1 Answer

11 votes

Answer:

(2, 5 )

Explanation:

y = 2x + 1 → (1)

3y = 4x + 7 → (2)

substitute y = 2x + 1 into (2)

3(2x + 1) = 4x + 7 ← distribute parenthesis on left side

6x + 3 = 4x + 7 ( subtract 4x from both sides )

2x + 3 = 7 ( subtract 3 from both sides )

2x = 4 ( divide both sides by 2 )

x = 2

substitute x = 2 into (1) for corresponding value of y

y = 2(2) + 1 = 4 + 1 = 5

solution is (2, 5 )

User Shevliaskovic
by
6.1k points